Collismycin C reduces HMGB1-mediated septic responses and improves survival rate in septic mice. Issue 1 (2nd January 2021) - Kim, Eonmi; Ku, Sae-Kwang; Yang, Sumin; Lee, Bong-Seon; Kim, Geum Jin; Choi, Hyukjae; Bae, Jong-Sup
Abstract: We examined the effects of a 2, 2′-bipyridine containing natural product, collismycin C on high mobility group box 1 (HMGB1, septic mediator)-mediated septic responses and survival rate in a mouse sepsis model. Collismycin C inhibited the HMGB1 release and downregulated HMGB1-mediated inflammatory responses in human endothelial cells. Collismycin C also inhibited HMGB1-induced hyperpermeability and leukocyte migration in mice. In addition, collismycin C treatment reduced CLP-induced HMGB1 release and sepsis-related mortality and pulmonary damage in vivo . Our results indicate that collismycin C is a potential therapeutic agent for the treatment of severe vascular inflammatory diseases by inhibiting HMGB1 signaling pathway. Abstract :